TOKOH EMANSIPASI WANITA ISLAM DI MESIR PADA ABAD KE 19 M - Erasiah Erasiah (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Egypt is one of the areas that are already well-known as a bag of pre- Islamic civilization of the world set foot there. That's the right word destined for the territory of the Nile valley civilization heritage of this. People with the name of the bag this civilization to this day still attached either at one of the area located in North Africa. In Egypt it is born leaders of Islamic thinkers who have ideas that are very brilliant and influential to this day in the Islamic world. Of the many characters who have ideas that are very brilliant, then on this occasion intends to discuss at length about the emancipation of women leaders in Egypt in the 19th century AD. Keywords: women and emancipationCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.98